2023
DOI: 10.1039/d2nr05444b
|View full text |Cite
|
Sign up to set email alerts
|

Emerging biotransduction strategies on soft interfaces for biosensing

Abstract: As a lab-on-soft biochip providing accurate and timely biomarker information, wearable biosensors can satisfy the increasing demand for intelligent e-health services, active disease diagnosis/therapy, and big bioinformation data. As biomolecules...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 109 publications
0
7
0
Order By: Relevance
“…Table 2 shows that the in-plane Young's moduli of 2D Janus P3m1 Zr 2 N 3 H, Hf 2 N 3 H, and Hf 2 N 3 F (155-188 N m À1 ) are smaller than those of well-known 2D materials, including graphene (342-366 N m À1 ) and h-BN (258-276 N m À1 ). 51 This suggests that 2D Janus P3m1 Zr 2 N 3 H, Hf 2 N 3 H, and Hf 2 N 3 F phases present a promising option for flexible electronic device design.…”
Section: Surface Functionalization Of 2d Janusmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 shows that the in-plane Young's moduli of 2D Janus P3m1 Zr 2 N 3 H, Hf 2 N 3 H, and Hf 2 N 3 F (155-188 N m À1 ) are smaller than those of well-known 2D materials, including graphene (342-366 N m À1 ) and h-BN (258-276 N m À1 ). 51 This suggests that 2D Janus P3m1 Zr 2 N 3 H, Hf 2 N 3 H, and Hf 2 N 3 F phases present a promising option for flexible electronic device design.…”
Section: Surface Functionalization Of 2d Janusmentioning
confidence: 99%
“…The H + /H 2 reduction potential was estimated using a standard of E(H + /H 2 ) = À4.44 eV + pH Â 0.06 eV with reference to the vacuum level, whereas the oxidation potential of O 2 /H 2 O was calculated from E(O 2 /H 2 O) = À5.67 eV + pH Â 0.06 eV. 51 In contrast to conventional 2D materials, there are vacuum level shifts between the two facets due to the Janus geometry. As depicted in Fig.…”
Section: Surface Functionalization Of 2d Janusmentioning
confidence: 99%
“…The analysis focuses on determining the optimal model use for the OER/ORR descriptor and reaction mechanism of each catalyst. 98,99 The detailed information of each descriptor is summarized in Table S15. †…”
Section: Machine Learningmentioning
confidence: 99%
“…[283,315] It has been shown that by controlling the crystallization process through the inclusion of additives such as phenethylamine iodide (PEAI) or SnF 2 , the operational lifetimes (time for the initial peak radiance of the LED to decrease by 50% under continuous operation) of FASnI 3 and CsSnBr 3 LEDs in an inert environment could exceed 10 and 30 hours (Figure 20b), respectively. [285,316] Recently, LEDs fabricated with 2D Sn-based perovskites have also gained more attention owing to their higher intrinsic stability in the air. Particularly, a pure-red EL with rather small FWHMs (less than 0.1 eV) have been demonstrated in (PEA) 2 SnI 4 as well as (TEA) 2 SnI 4 LEDs, and this EL was stable in a wide voltage range [299,317,57] (Figure 20b).…”
Section: Sn and Ge-based Perovskite Ledsmentioning
confidence: 99%